LACTB promotes metastasis of nasopharyngeal carcinoma via activation of ERBB3/EGFR-ERK signaling resulting in unfavorable patient survival. (1st February 2021) - Peng, Li-Xia; Wang, Ming-Dian; Xie, Ping; Yang, Jun-Ping; Sun, Rui; Zheng, Li-Sheng; Mei, Yan; Meng, Dong-Fang; peng, Xing-Si; Lang, Yan-Hong; Qiang, Yuan-Yuan; Li, Chang-Zhi; et al.
Abstract: Nasopharyngeal carcinoma (NPC) originates in the nasopharyngeal epithelium and has the highest metastatic rate among head and neck cancers. Distant metastasis is the main reason for treatment failure with the underlying mechanisms remaining unclear. By comparing the expression profiling of NPCs versus non-cancerous nasopharyngeal tissues, we found LACTB was highly expressed in the tumor tissues. We found that elevated expression of the LACTB protein in primary NPCs correlated with poorer patient survival. LACTB is known to be a serine protease and a ubiquitous mitochondrial protein localized in the intermembrane space. Its role in tumor biology remains controversial. We found that the different methylation pattern of LACTB promoter led to its differential expression in NPC cells. Overexpressing LACTB in NPC cells promoted their motility in vitro and metastasis in vivo . While knocking down LACTB reduced the metastasis capability of NPC cells. However, LACTB did not influence cellular proliferation. We further found the role of LACTB in promoting NPC metastasis depended on the activation of ERBB3/EGFR-ERK signaling, which in turn, affected the stability and the following acetylation of histone H3. These findings may shed light on unveiling the mechanisms of NPC metastasis. Highlights: We have demonstrated for the first time that LACTB is the key metastasis promoter in NPC. We have found that elevated LACTB in primary NPC is an independent unfavorable prognostic factor for NPC patient survival. We have identified the mechanism through which the LACTB promotes metastasis via activation of ERBB3/EGFR-ERK signaling. Histone H3 degradation is partially controlled by LACTB, which in turn affects the LACTB-promoted metastasis of NPC cells.